Médecine et droit, compétition ou collaboration ? - Alessandro Pastore (Histoire, Médecine et Santé, 2017)
This paper sheds light on two treatises relating to the practice of criminal justice and useful to issue guidelines for investigating and judging murder, sexual offences, and other violent crimes. The first part of the article examines Il giudice criminalista, written by Antonio Maria Cospi (1638); the second part analyses the Pratica universale, written by Marcantonio Savelli (1665). Both books point out that expert medical testimony played a crucial role in the criminal proceedings. Due to the increasing knowledge of the human body during the Renaissance and the early modern period, the physician plays a key role working alongside the judge. The jurists and the judicial authorities were not always unanimous about the interaction between law and medicine, but they had to recognise that the performing of medical expertise was a practice of vital importance.